UNDERSTANDING THE DYNAMICS OF ENTREPRENEURIAL PASSION IN ENTREPRENEURSHIP STUDENTS - Atlansyah, Enrita; Nuringsih, Kartika (International Journal of Application on Economics and Business, 2023)
The goal of this study is to analyze the shaping of entrepreneurial passion among students in the practice of entrepreneurial learning at the one university in Jakarta, Indonesia. Exploring this passion is based on two exogenous variables namely emotional support and perceived competence. Students of the Management Program at the Faculty of Economics and Business of Universitas Tarumanagara were involved as source persons in this research. The purposive sampling method is considered for the selection of samples. Some testing stages were used to analyze data including validity, reliability, and structural regression by using the software of Smart-Pls. The result shows both exogenous variables giving significantly affect entrepreneurial passion. Further effects establish good reliability on these constructs and most indicators are valid. Otherwise, found some indicators got a less score on the loading factor so three items are not accurate to measure entrepreneurial passion and one item is less useful to indicate perceived competence. Based on these results, the entrepreneurial education ecosystem needs to improve these items, so students will be more understand the dynamics of entrepreneurial passion specifically for inventing, founding, and developing their venture. It is useful as a mechanism for encouraging the desire of students for entrepreneurial activity.